Self-Resilience of Qur'an Memorizers in University - Afifah, Rohmatul; Setiyowati, Arbin Janu; Probowati, Devy (Education and Development Research, 2026)
This study aims to understand the resilience of students who memorize the Qur'an at a state university in Malang, Indonesia, specifically in the Faculty of Education, based on the seven aspects of resilience identified by Reivich and Shatte. This study uses a qualitative approach with a phenomenological method. Data were collected through interviews, observations, and documentation with two students who memorize the Qur'an at the Faculty of Education and four supporting informants. The research subjects were selected purposively, consisting of: 1) students who memorize the Qur'an, 2) students enrolled at one of the state universities in Malang City and at the Faculty of Education, and 3) students in semesters 2-6, 4) Students who are still in the process of memorizing (not yet completed), and 5) Willing to be research subjects. The findings show that the resilience of students who memorize the Qur'an is formed through seven aspects of resilience identified by Reivich and Shatte, and is influenced by external factors, namely social support. This study recommends that the guidance and counseling center at the state university in Malang, provide individual or group counseling focused on the problems experienced by students who memorize the Qur'an. Then, hold workshops or seminars on strategies for maintaining resilience, stress management, and increasing motivation to memorize, and finally, create information services in the form of posters on maintaining resilience amid busy college activities and memorization.